(untitled) (Sociologisk Forskning, 2022)
Sugar dating is a by and large new and growing phenomenon within the sex and intimacy industry, centred on web sites tailored to facilitating the practice. The phenomenon overlaps significantly with prostitution but is marketed as something else. In this article, based on interviews with 15 “sugar babies” and 9 “sugar daddies” with experience of heterosexual sugar dating, we investigate the strategies that sugar daters use to demarcate their experiences from prostitution. We show that both the women and the men carry out a linguistic and practical “relational work” serving to dissociate sugar dating either from prostitution as such or from what the interview participants regarded as real prostitution. The relational work pivots around five central themes: how the compensation is labelled, how the compensation is carried out, the woman’s sexual voluntariness, mutual pleasure, and dating similarity. We contend that the interview participants’ distancing from prostitution may be interpreted not only as a way of fending off associations with a stigmatized practice, but also as an expression of the fact that the interview persons have charged conceptions of prostitution that they have difficulties aligning with their own experiences.